INFLUENCE OF BIOLOGICALLY ACTIVE SUBSTANCES ON TOMATO YIELD AND QUALITY - G. I. Yarovoy; V. I. Kuzmenko (Овощи России, 2017)
The study of influence of growth regulators and biopreparations affecting on decrease of disease development, increase of yield capacity and final product quality was carried out in tomato. It was shown that all preparations were effective in decreasing the process of diseases development and increasing the yield capacity and product quality. The studies were carried out in the experimental fields at the Institute of Vegetables and Melons NAAS, in Ukraine in 2011-2012. The field studies were performed according to ‘Methodology of Experimental Work in Vegetable and Melon Growing’ on area sown with cultivars ‘Karas’ and ‘Kremenchugskiy’. The fungicides ‘Mars U 77%’, ‘Vimpel with Fitotsid’, ‘Vermistim’ wth ‘Azotofit’ and ‘Bioglobin’ with ‘Azotofit’ were used on cultivars of tomato, as control were the plants without treatment. It was determined that all preparations decreased the development of diseases. On average, the development of early dry spot had decreased by 12.2–16.1% and anthracnose by 10.0–12.6% in the cultivars ‘Kremenchugskiy’ and ‘Karas’. Thus, biopreparations used on the varieties ‘Kremenchugskiy’ and ‘Karas’ were effective in decrease of disease development, such as early dry spot, anthracnose, in a range of 39.1–52.7 %. Generally, during observation period the efficacy index of the preparations ‘Vermistim’ with ‘Azotofit’, ‘Bioglobin’ with ‘Azotofit’ was higher than others preparations on the varieties ‘Kremenchug and ‘Karas’ against early dry spot (48.3–50.9%, 50.3–52.7%) and anthracnose (46.1–47.0%, 47.6–48.5%). The results showed that the vast majority of biological preparations, phytohormones used against diseases in tomato crops of varieties ‘Kremenchugskiy’ and ‘Karas’, were effective in a range of 39.1-52.7% and also maintained the tomato yield within 2.8-5.1 t/ha or 8.1- 13.9%. The biological preparations, phytohormones improved common biochemical parameters.